Rent seeking and business organizations: an explanatory study of business organization’s role during Brazil’s trade liberalization era - Bouyer, Timothee Francois Marie Andre (2017)
Brazil partially shifted from state-led development to market economy following its switch to democracy. This affected the economy in two ways: first the state initiated a wave of privatization in the wake of the fiscal crisis under President Collor. Second, the economy started opening up to international competition through the enactment of certain trade reforms. However, the economy still displays erratic levels of protectionism. The literature on rent seeking argues that organized interest groups devote resources to capture and try to influence and neutralize the liberalization of the economy, which would endanger the rents they benefit from under existing rules. After decades of state nurturing under the ISI model, the business sector in Brazil was crucial to shaping the path for a new growth model. However, their role in promoting trade openness was far more nuanced. The present work looks at business groups in Brazil since the second half of the twentieth century and the role they played before and during the transition and how their opposition to trade reforms suggests potential rentseeking behaviors. The transition to democracy witnessed the emergence of new business organizations with independent actions that I will account for in this paper. Business organizations were not united at the time of economic reforms and thus reacted differently according to the interests of their members. Institutional factors, amongst which the rise of a new civil society, as well as conjectural factors further constrained the path of economic reforms.